Turbulence: A Corporate Perspective on Collaborating for Resilience - Roland Kupers (Amsterdam University Press, 2014)
The ever tighter coupling of our food, water and energy systems, in the context of a changing climate is leading to increasing turbulence in the world. As a consequence, it becomes ever more crucial to develop cities, regions, and economies with resilience in mind. Because of their global reach, substantial resources, and information-driven leadership structures, multinational corporations can play a major, constructive role in improving our understanding and design of resilient systems. This volume is the product of the Resilience Action Initiative, a collaboration among Dow, DuPont, IBM, McKinsey en Co., Shell, Siemens, Swiss Re, Unilever, and Yara designed to explore possible corporate contributions to global resilience, especially at the nexus of water, food and energy. Aggressively forward-thinking, and consistent with an enlightened self-interest, the ideas considered here represent a corporate perspective on the broad collaborations required for a more resilient world.
Keywords: 300; Resilience models; water-energy-food nexus; Klimawandel; Energieversorgung; Wirtschaftliche Anpassung; Welt